ANALISIS DAYA GABUNG HASIL PERSILANGAN DIALEL BEBERAPA VARIETAS PADI (Oryza sativa L.) MENGGUNAKAN METODE GRIFFING - Rianti, Sofi; Sudharmawan, Anak Agung Ketut; Listiana, Baiq Erna (Department of Agronomy, Faculty of Agriculture, University of Mataram and Indonesian Society of Agronomy, NTB Branch, 2023)
This research aimed to determine the general combining ability and special combining ability of the cross-dialel crossing results of several varieties of rice plants using the Griffing method. The study was conducted in technical irrigated rice fields, the Experimental Garden of the Faculty of Agriculture, University of Mataram in the Village of Nyur Lembang, Narmada District, West Lombok Regency in February to July 2019. The experimental design used in this study was a Randomized Block Design (RAK) using the dialel Griffing II method consisting of 4 elders and F1 crossing results. The results showed that the results of the analysis of the combining ability of four rice elders and the results of crossing f1 using the Griffing II method. Of the seven characters have a positive joining power.